Enhanced Drug Release of Poly(lactic-co-glycolic Acid) Nanoparticles Modified with Hydrophilic Polymers: Chitosan and Carboxymethyl Chitosan - Diah Lestari; Noverra Mardhatillah Nizardo; Kamarza Mulia (Indonesian Journal of Chemistry, 2022)
The biodegradable polymer poly(lactic-co-glycolic acid) (PLGA) is a biomaterial with great potential as a drug delivery carrier and a tissue engineering scaffold. Using diclofenac sodium (DS) as a drug model, PLGA/DS nanoparticles were synthesized by modification with two hydrophilic polymers: chitosan and carboxymethyl chitosan (CMCh). The introduction of chitosan and CMCh enhances the efficiency encapsulation, capacity loading of the nanoparticles, and DS release at pH 6.8 and minimum release at pH 1.2. Synthesis of nanoparticles was carried out using a double emulsion (water/oil/water) solvent evaporation method. Characterization using an Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectrophotometer indicates that the interaction between DS and polymer on nanoparticles is non-covalent with a spherical shape based on a transmission electron microscope (TEM) and scanning electron microscope (SEM) characterization. From the various formulation studied, nanoparticles with the ratio chitosan-PLGA-DS and CMCh-PLGA-DS of 2:20:4 proved to be the optimum model carrier with the required release profile and could be the alternative for DS delivery systems.